"Is This Ethical?" A Survey of Opinion on Principles and Practices of Document Design - Dragga, Sam (Technical Communication, 1996)
In a national survey, 500 technical communicators and 500 technical communication teachers were asked to assess the ethics of seven document design cases. According to the 455 respondents, manipulating typography and leading to fit more or less information on a page and using persuasive coloring or spacing are ethical practices, while the manipulation of pictorial illustrations and the distortion of graphics are unethical. Opinion on using typography to decrease readability is divided. In five of the seven cases, women are consistently more lenient or men consistently more strict in their evaluations of ethics. Respondents offered nine different types of explanations for their answers: common practices, specifications, reader's responsibility, writer's responsibility, writer's intentions, consequences, judgments, principles, and insufficient information. The explanation most often given was consequences, indicating a "goalbased" philosophy of ethics.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzA4ODA2NQ